00.03: European research on steel structures in seismic areas. (13th September 2017) - Mazzolani, Federico M.
ABSTRACT: In Europe the research activities on steel structures in seismic areas is very intense and productive since the '80s of the last century. Many research projects have been developed. In particular, the activity started within the Technical Committee 13 (seismic design) of ECCS deeply contributed to the scientific debate and to the genesis of current Eurocode 8, which is currently under maintenance. This paper summarizes the main topics already consolidated and the related research activities currently ongoing, together with the ones needing further developments, in order to highlight the research perspectives of the European community of experts working on the field of steel structures in seismic areas. In particular, the discussion focuses on material properties, local ductility, full strength and dissipative joints, innovative types of links in eccentrically braced frames, capacity design rules, cold‐formed applications, new structural types and devices, the use of steel in structural consolidation.